Diel‐ and temperature‐driven variation of leaf dark respiration rates and metabolite levels in rice. Issue 1 (7th June 2020) - Rashid, Fatimah Azzahra Ahmad; Scafaro, Andrew P.; Asao, Shinichi; Fenske, Ricarda; Dewar, Roderick C.; Masle, Josette; Taylor, Nicolas L.; Atkin, Owen K.
Summary: Leaf respiration in the dark ( R dark ) is often measured at a single time during the day, with hot‐acclimation lowering R dark at a common measuring temperature. However, it is unclear whether the diel cycle influences the extent of thermal acclimation of R dark, or how temperature and time of day interact to influence respiratory metabolites. To examine these issues, we grew rice under 25°C : 20°C, 30°C : 25°C and 40°C : 35°C day : night cycles, measuring R dark and changes in metabolites at five time points spanning a single 24‐h period. R dark differed among the treatments and with time of day. However, there was no significant interaction between time and growth temperature, indicating that the diel cycle does not alter thermal acclimation of R dark . Amino acids were highly responsive to the diel cycle and growth temperature, and many were negatively correlated with carbohydrates and with organic acids of the tricarboxylic acid (TCA) cycle. Organic TCA intermediates were significantly altered by the diel cycle irrespective of growth temperature, which we attributed to light‐dependent regulatory control of TCA enzyme activities. Collectively, our study shows that environmental disruption of the balance between respiratory substrate supply and demand is corrected for by shifts in TCA‐dependent metabolites.